STRATEGI E- MARKETING DAN BRAND AWARENESS MELALUI PEMASARAN ONLINE MEDIA SOSIAL TIKTOK TERHADAP MINAT BELI KONSUMEN PADA CAFE COFFEE ISEFF DI KABUPATEN TANGERANG: Indonesia - Putri Nurjanah, Putri Nurjanah; Wahyono, Agus (Jurnal Manajemen, 2023)
This study aims to determine whether Consumer Purchase Interest (Y), E-Marketing Strategy (X1), Brand Awareness (X2), Online Marketing (Z) Social Media TikTok has a positive, significant effect on Cafe Coffee Iseff in Tangerang Regency. The research methodology uses quantitative methods, on primary data obtained from distributing questionnaires to 100 respondents who wish and who have visited, and the research results are obtained from the answers of respondents using a Likert scale. Using the path analysis test tool in the SPSS application version 25.0 2022. The results of the study stated that the E-Marketing Strategy had no direct effect on Online Marketing. Brand Awareness has a direct, significant effect on Online Marketing. The E-Marketing Strategy has a positive, significant direct effect on Consumer Purchase Interest. Brand Awareness has no direct effect on Consumer Purchase Interest. Online Marketing has a direct effect on Consumer Purchase Interest. The E-Marketing Strategy has no indirect effect on Consumer Purchase Interest through Online Marketing. Brand Awareness has an indirect effect on Consumer Purchase Interest through Online Marketing.